2012
DOI: 10.1007/s00776-012-0262-4
|View full text |Cite
|
Sign up to set email alerts
|

Repair of segmental bone defects in rabbit tibia promoted by a complex of β-tricalcium phosphate and hepatocyte growth factor

Abstract: Background Segmental bone defect repair remains a clinical and scientific challenge with increasing interest focused on bone tissue engineering. Clinical studies are ongoing to address application of hepatocyte growth factor (HGF) for treatment of some diseases; however, the use of HGF in bone tissue engineering has not been addressed. This study was performed to evaluate the effect of HGF in a complex of b-tricalcium phosphate (b-TCP) and collagen in repairing segmental bone defects. Methods Segmental bone de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
0
12
0
2
Order By: Relevance
“…In the defects treated with BMP-2+HGF, most of the gelatin sponge was absorbed and replaced by newly formed bone with bone marrow four weeks after surgery. Since HGF is a potent antifibrotic agent 53) and facilitates the resorption of the biological scaffold 54) comprising extracellular matrix, HGF may help to promote the absorption of the gelatin sponge, which could improve the environment for bone regeneration in the defect area. However, the impact of HGF on the degradation of extracellular matrix is still under investigation.…”
Section: The Effect Of Hgf On Angiogenesis During Bone Regeneration Imentioning
confidence: 99%
“…In the defects treated with BMP-2+HGF, most of the gelatin sponge was absorbed and replaced by newly formed bone with bone marrow four weeks after surgery. Since HGF is a potent antifibrotic agent 53) and facilitates the resorption of the biological scaffold 54) comprising extracellular matrix, HGF may help to promote the absorption of the gelatin sponge, which could improve the environment for bone regeneration in the defect area. However, the impact of HGF on the degradation of extracellular matrix is still under investigation.…”
Section: The Effect Of Hgf On Angiogenesis During Bone Regeneration Imentioning
confidence: 99%
“…Plain scaffolds and scaffolds loaded with MSC provided less bone formation than the autograft and rhBMP-7 group [19]. Goshima et al [20] performed a study on segmental bone defect repair in tibial shafts of rabbits using β-tricalcium phosphate (β-TCP) scaffolds loaded with hepatocyte growth factor (HGF). They found that HGF-loaded scaffolds promoted mineralisation, angiogenesis, new bone formation and β-TCP absorption [20].…”
Section: Discussionmentioning
confidence: 99%
“…Goshima et al [20] performed a study on segmental bone defect repair in tibial shafts of rabbits using β-tricalcium phosphate (β-TCP) scaffolds loaded with hepatocyte growth factor (HGF). They found that HGF-loaded scaffolds promoted mineralisation, angiogenesis, new bone formation and β-TCP absorption [20]. Sauerbier et al [21] and Rickert et al [22] performed randomised controlled clinical trials to investigate formation of new bone in patients with severe atrophy of the maxillary sinus.…”
Section: Discussionmentioning
confidence: 99%
“…Increased β-TCP resorption indicates greater repair of the bone defect. After eight weeks a slight amount of bone formation was visible in the untreated controls, while both treatment groups showed a substantial increase in bone density and volume 60 . Additionally, the group treated with the combination of β-TCP, collagen, and HGF had a larger area of new bone formation at weeks 2, 4, and 6 and smaller area of β-TCP, suggesting more β-TCP was resorbed and replaced by newly formed bone 60 .…”
Section: 2 Effects Of Hgf In the Context Of Osteogenesismentioning
confidence: 93%
“…The local expression of HGF in the microenvironment of a bone fracture showed enhanced healing of the bone fracture in rabbits 59 . Furthermore, a rabbit model of a bone defect showed that HGF in combination with β-tricalcium phosphate (β-TCP) and collagen was more effective than the β-TCP and collagen treatments alone or the untreated control 60 . β-TCP is used as a bone substitute when repairing bone defects due to its resorbability and biocompatibility, allowing it to enable surface bone growth.…”
Section: 2 Effects Of Hgf In the Context Of Osteogenesismentioning
confidence: 99%